2012
DOI: 10.1111/eci.12021
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and platelet responses to aspirin in patients with coronary artery disease

Abstract: We conclude that LTA is a more sensitive marker of aspirin resistance than is flow cytometry for P-selectin and PCA-1, and that aspirin response has no influence on vascular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
1
15
0
2
Order By: Relevance
“…Abbreviations: OR, odds ratio; 95% CI, 95% confidence interval; PCSK9, proprotein convertase subtilisin/kexin type 9; PLT, platelet; PCT, plateletcrit; PDW, platelet distribution width; MPV, mean platelet volume; BMI, body mess index; CAD, coronary artery disease. tially important clinical issue in the present study 23) . In addition, the sample would have been very small if the factor of aspirin/anti-platelet administration had been considered.…”
Section: Discussionmentioning
confidence: 68%
“…Abbreviations: OR, odds ratio; 95% CI, 95% confidence interval; PCSK9, proprotein convertase subtilisin/kexin type 9; PLT, platelet; PCT, plateletcrit; PDW, platelet distribution width; MPV, mean platelet volume; BMI, body mess index; CAD, coronary artery disease. tially important clinical issue in the present study 23) . In addition, the sample would have been very small if the factor of aspirin/anti-platelet administration had been considered.…”
Section: Discussionmentioning
confidence: 68%
“…Some data in favor of the former notion was provided in the above-mentioned study by Yong et al [33], in which EMMPRIN expression in circulating platelets obtained from the coronary sinus of stable CAD patients was significantly higher than in those obtained from their peripheral vein, the difference was not significant for soluble EMMPRIN levels in the plasma. There are also data in favor of the latter notion: it has been shown that aspirin reduced the platelet expression of P-selectin and PAC-1 [36] and clopidogrel reduced the platelet expression of PAC-1 and circulating levels of soluble P-selectin [37], and that both of these proteins were positively and highly correlated with platelet EMMPRIN expression [10]. Similarly, fluvastatin, has been shown to reduce EMMPRIN expression in macrophages [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HPR detected by PFA-100 does not correlate with the results of LTA-AA: none of the 116 patients with a definition of HPR at T 0 exhibited a LTA-AA >20%, the cut-off value accepted to describe a condition of aspirin resistance [19]. …”
Section: Discussionmentioning
confidence: 99%